Effect of a thin organosilicon layer prepared by atmospheric pressure plasma on wood flame retardancy. Issue 11 (15th June 2022) - Soula, Marie; Profili, Jacopo; Caceres‐Ferreira, Williams; Samyn, Fabienne; Duquesne, Sophie; Falzacappa, Emanuele V.; Scopece, Paolo; Laroche, Gaétan; Landry, Véronic
Abstract: In a high‐rise building, due to the risk of flame spread and strict regulations associated, wood use is limited for interior finishes. This study aimed to evaluate the effect of a thin organosilicon layer (∼500 nm) prepared by atmospheric pressure plasma on the fire behavior of a wood substrate. The coating was deposited from hexamethyldisiloxane in argon on both untreated wood and wood with a preparatory coating of primer. The primer reduces the presence of cracks in the plasma layer and ensures more homogenous coverage of the substrates. Finally, the flame retardancy analysis highlights an improvement in fire behavior only when the primer is used. Our study suggests that plasma thin deposition has a synergic effect with primer to fireproof wood. Abstract : Wood flammability is a limiting factor in its use in construction, despite its low cost and environmental impact. This article explores this interest in using atmospheric plasma jet deposition of hexamethyldisiloxane to increase the wood fire‐retardancy. Chemical and morphological analysis demonstrate that the plasma deposition is more homogenous when a primer coating is applied on wood. The homogeneity of the deposition has a positive impact on wood fire retardancy.